2014
DOI: 10.1097/cmr.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of developing cutaneous malignant melanoma is associated with variation in pigmentation genes and VDR, and may involve epistatic effects

Abstract: Cutaneous malignant melanoma (CMM) is a malicious human skin cancer that primarily affects individuals with light pigmentation and heavy sun exposure, but also has a known familial association. Multiple genes and polymorphisms have been reported as low-penetrance susceptibility loci for CMM. Here, we examined 33 candidate polymorphisms located in 11 pigmentation genes and the vitamin D receptor gene (VDR) in a population of 130 cutaneous melanoma patients and 707 healthy controls. The genotypes obtained were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 87 publications
(151 reference statements)
1
13
1
Order By: Relevance
“…The common explanation of lighter skin color does not explain this dramatic increase because, besides our findings, others found no significant difference exists in the CMM incidence between skin type I/II and III/IV Europeans (p = 0.79) 50 or Americans 23 . One plausible explanation is the hormonal changes that occur during puberty associated with growing androgenic body hair, the distribution of which 51 aligns well with the distribution of CMM 9,52 .…”
Section: Discussioncontrasting
confidence: 49%
“…The common explanation of lighter skin color does not explain this dramatic increase because, besides our findings, others found no significant difference exists in the CMM incidence between skin type I/II and III/IV Europeans (p = 0.79) 50 or Americans 23 . One plausible explanation is the hormonal changes that occur during puberty associated with growing androgenic body hair, the distribution of which 51 aligns well with the distribution of CMM 9,52 .…”
Section: Discussioncontrasting
confidence: 49%
“…SNP rs16891982 at locus 5p13, a nonsynonymous SNP (Phe374Leu) in SLC45A2 , has been associated with SCC (Stacey et al, 2009), BCC (Stacey et al, 2009), and CMM (Barrett et al, 2011; Stacey et al, 2009; Guedj et al, 2008; Duffy et al, 2010b; Ibarrola-Villava et al, 2012; Kosiniak-Kamysz et al, 2014; Fernandez et al, 2008) as well as eye, hair and skin color (Duffy et al, 2010b; Branicki et al, 2009; Eriksson et al, 2010; Stokowski et al, 2007; Soejima and Koda, 2007; Liu et al, 2015). SLC45A2 encodes a membrane-associated transporter enzyme, and loss of SLC45A2 activity has been found to disrupt post-Golgi-level trafficking of tyrosinase to the melanosomes (Newton et al, 2007) where melanin is synthesized and stored.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, OR ~ 1.17 may suggest the problem with statistical power to detect association between eye colour and rs12203592 in this study. Interestingly, IRF4 shows ambiguous pattern of association with cutaneous cancers in various populations [ 37 41 ]. Pietroni et al has reported three IrisPlex SNPs to be the only informative for eye colour prediction, and this set comprised rs12913832 in HERC2 , rs1800407 in OCA2 and rs16891982 in SLC45A2 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%